Effect of different organic inputs on agronomic and economic performance of sesame under rainfed conditions of North Maharashtra: Effect of different organic inputs on agronomic and economic performance of sesame under rainfed conditions of North Maharashtra - B D MALUNJKAR,; S S PATIL, (Journal of Oilseeds Research, 2023)
A field experiment was conducted at Oilseeds Research Station, MPKV, Jalgaon to assess the performance of most suitable organic source for sesame production and its economics during the kharif season of 2021. Application of FYM on N equivalent basis + foliar application of 3% Panchgavya at flowering and capsule formation stage + Foliar application of Pseudomonas and Azotobactor 2 lit /ha both + soil application of Pseudomonas and Azotobactor (2.5 lit /ha + 200 kg FYM) recorded numerically higher seed yield ( 568 kg/ ha) over rest of the treatments, whereas higher net returns ( 26078/ha) and B: C ratio of 2.13 was obtained under application of RDF ( 50 % N as basal and remaining 50 % in 2 split doses) over rest of the organic sources.